1986
DOI: 10.1002/art.1780290809
|View full text |Cite
|
Sign up to set email alerts
|

Increased calcification of growth plate cartilage as a result of compressive force in vitro

Abstract: The influence of intermittent compressive force (ICE') and of continuous compressive force (CCF) on calcification of growth plate cartilage was investigated, using organ cultures of fetal mouse cartilaginous long bone rudiments. Sixteen-day-old metatarsal rudiments, still consisting of uncalcified cartilage, were isolated and cultured for 5 days. Initial calcification of hypertrophic Cartilage occurred under control conditions (atmospheric pressure), and under the influence of ICF or CCF by intermittently or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(71 citation statements)
references
References 23 publications
1
70
0
Order By: Relevance
“…21,22,[24][25][26] Experimental data obtained by applying intermittent and continuous compressive forces to the 16-day-old metatarsal rudiment of mouse embryo in organ culture demonstrated that the mineral apposition in the primary ossification site in the center of the metatarsal cartilage rudiment is accelerated, with intermittent forces twice as effective as continuous forces. 27 This study suggests that mechanical stresses accelerate the formation of the primary ossification site during prenatal development. 27 In a follow-up study using finite element modeling, distortional strain was shown to be too small (about 2 microstain) to have stimulated ossification of the 16-day-old embryonic metatarsal rudiment in organ culture; instead, hydrostatic pressure is responsible for the observed epiphyseal ossification.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…21,22,[24][25][26] Experimental data obtained by applying intermittent and continuous compressive forces to the 16-day-old metatarsal rudiment of mouse embryo in organ culture demonstrated that the mineral apposition in the primary ossification site in the center of the metatarsal cartilage rudiment is accelerated, with intermittent forces twice as effective as continuous forces. 27 This study suggests that mechanical stresses accelerate the formation of the primary ossification site during prenatal development. 27 In a follow-up study using finite element modeling, distortional strain was shown to be too small (about 2 microstain) to have stimulated ossification of the 16-day-old embryonic metatarsal rudiment in organ culture; instead, hydrostatic pressure is responsible for the observed epiphyseal ossification.…”
Section: Introductionmentioning
confidence: 76%
“…27 This study suggests that mechanical stresses accelerate the formation of the primary ossification site during prenatal development. 27 In a follow-up study using finite element modeling, distortional strain was shown to be too small (about 2 microstain) to have stimulated ossification of the 16-day-old embryonic metatarsal rudiment in organ culture; instead, hydrostatic pressure is responsible for the observed epiphyseal ossification. 28 Using a finite element model, Wong and Carter 25,26 postulated that the externally applied hydrostatic pressure, while purely hydrostatic at the rudiment end, produces significant shear stresses at the cartilage/calcified cartilage interface.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…While the literature describing in vivo and in vitro investigations of the mechanobiology of embryonic limb development is often disjointed and contradictory, a number of important findings clearly establish a central role of mechanical factors. The level of tension experienced by cultured embryonic bone rudiments has been shown to regulate the rate of bone formation (Glucksmann 1939;Glucksmann 1942), while intermittent compression of cultured embryonic mouse long bone rudiments has been shown to increase calcification of the growth plate cartilage (Klein-Nulend et al, 1986). In vitro studies have also demonstrated that cartilaginous tissue in the membrane bones of the embryonic chick will form in response to the mechanical signals generated by movement (Hall 1968).…”
Section: Repairmentioning
confidence: 99%
“…During movement compressive loading and unloading of hydrated tissues result in changes of the interstitial fluid pressure 26. Hydrostatic pressure has further been shown to enhance mineralization and bone formation when applied to osteoblast‐like cells, cell‐seeded constructs, and ex‐vivo organotypically cultured chick femurs 25, 26, 27…”
Section: Introductionmentioning
confidence: 99%